2014
DOI: 10.1124/jpet.113.210799
|View full text |Cite
|
Sign up to set email alerts
|

The Neurokinin-1 Receptor in Addictive Processes

Abstract: Stress can trigger drug-seeking behavior, increase selfadministration rates, and enhance drug reward. A number of stress-related neuropeptides have been shown to mediate these behavioral processes. The most studied peptide in this category is corticotropin-releasing hormone (CRH), which has been shown to mediate stress-induced reinstatement of drug seeking, escalated self-administration, and drug withdrawal, but it does not seem to be involved in baseline drug self-administration or cue-induced reinstatement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…The dose chosen for our study was 80 mg/day, based on an earlier study of pruritus by Ständer et al (7). Regarding the dose of aprepitant, it has been suggested that, for treatment of depression, near complete receptor occupancy for the NK-1R antagonist is needed, and that an occupancy of below 90% may be ineffective (15). In a study of co-morbid alcohol dependence and post-traumatic stress disorder a dosage of 125 mg/day for 4 weeks was used, based on positron emission tomography studies reporting > 90% central receptor occupancy at this dose (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose chosen for our study was 80 mg/day, based on an earlier study of pruritus by Ständer et al (7). Regarding the dose of aprepitant, it has been suggested that, for treatment of depression, near complete receptor occupancy for the NK-1R antagonist is needed, and that an occupancy of below 90% may be ineffective (15). In a study of co-morbid alcohol dependence and post-traumatic stress disorder a dosage of 125 mg/day for 4 weeks was used, based on positron emission tomography studies reporting > 90% central receptor occupancy at this dose (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, no effect was found. In addition, the influence of polymorphism of the tachykinin receptor (TacR) -1 gene may be of importance (15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the efficacy of this drug could be tested in clinical trials for psychiatric conditions mediated by inflammation. While past clinical trials using NK1R antagonists have produced mixed results, negative findings have possibly been influenced by complex factors including drug dosing and pharmacogenetic interactions (see [45,46] for discussion of this topic).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-amygdala infusion of the NK1R antagonist L822429 reduced alcohol self-administration in P rats while injections in the PFC did not (Schank et al, 2013). The amygdala is a component of the extended stress system, thus may play an important role in motivating drug seeking (reviewed by Schank, 2014). In fact, some preclinical studies indicate that NK1R antagonists may suppress stress-mediated alcohol relapse.…”
Section: Substance Pmentioning
confidence: 99%